If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -32 = 6x + 23 Reorder the terms: -32 + x = 6x + 23 Reorder the terms: -32 + x = 23 + 6x Solving -32 + x = 23 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -32 + x + -6x = 23 + 6x + -6x Combine like terms: x + -6x = -5x -32 + -5x = 23 + 6x + -6x Combine like terms: 6x + -6x = 0 -32 + -5x = 23 + 0 -32 + -5x = 23 Add '32' to each side of the equation. -32 + 32 + -5x = 23 + 32 Combine like terms: -32 + 32 = 0 0 + -5x = 23 + 32 -5x = 23 + 32 Combine like terms: 23 + 32 = 55 -5x = 55 Divide each side by '-5'. x = -11 Simplifying x = -11
| 4+3x=.25x-2 | | 0=-5+b | | 2x-4=2x+-2+3 | | y=375-50(15-1) | | -56+4x=10x+16 | | 4-3f=7 | | -12-92=183-x | | -3(x-9)= | | (b+1)*(b-1)= | | 7=48+x | | 4(5y-5)-(3y+8)= | | -9x+15=-4x-70 | | 4x^2+12x+c=y | | 5h-(h+8)=2n | | 6(5a+4)+5a=-11 | | -2(x+2)-3=5 | | -x-(13+4x)=-3(5-9x)+3k | | 2x^2+5x^2-7x-3= | | 2=4r | | 7x-(6x+5)=6x-40 | | 2x^3-6x^2-141x+6=0 | | 2(h+9)-6= | | 6-8(n-4)=-8n+37 | | 0.5x+8=3x+5 | | 10x-75=5x+30 | | w+14=18 | | 6x+10-8x=15-13x+11x-5 | | -10(-3x+3)=30+10x | | (3+x)4+(5x)=66 | | 20-0.5y=12.5 | | 20x-7-5=-52 | | -6(2+2x)=-24 |